Incentives and Disincentives for the Use of OpenCourseWare - Arendt, Anne M.; Shelton, Brett E. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This article examines Utah residents’ views of incentives and disincentives for the use of OpenCourseWare (OCW), and how they fit into the theoretical framework of perceived innovation attributes established by Rogers (1983). Rogers identified five categories of perceived innovation attributes: relative advantage, compatibility, complexity, trialability, and observability. A survey instrument was developed using attributes that emerged from a Delphi technique with input from experts in the OCW field. The survey instrument was sent to 753 random individuals between 18 and 64 years of age throughout Utah. Results indicated that the greatest incentives for OCW use were the following: (a) no cost for materials, (b) resources available at any time, (c) pursuing in depth a topic that interests me, (d) learning for personal knowledge or enjoyment, and (e) materials in an OCW are fairly easy to access and find. The greatest disincentives for OCW use were the following: a) no certificate or degree awarded, (b) does not cover my topic of interest in the depth I desire, (c) a lack of professional support provided by subject tutors or experts, (d) a lack of guidance provided by support specialists, and (e) the feeling that the material is overwhelming. The authors recommend that institutions work to transition some OCW users into degree-granting paid programs as well as adopt a marketing campaign to increase awareness of OCW. Additionally, OCW websites should make their content available to recommendation engines such as ccLearn DiscoverEd, OCW Finder, or OER Recommender and should reciprocally link to one or more of these sites.